Wind Power Feasibility Study in Boyacá (Revista de Diavulgación L'esprit Ingénieux, 2024)
In our environment, electrical energy sources are not the most optimal due to the materials and changes made to the environment, therefore, it is necessary to look for methodologies that do not affect and influence climate change, for this, renewable energies such as the wind, The Department of Boyacá has a topography of mountains and bombastic winds, which makes it a favorable condition in renewable energy resources associated with the wind, with wind speeds equal to or greater than 5 m/s in several months of the year. For this reason, it represents an ideal option for the implementation of new Non-Conventional Sources of Renewable Energy such as wind energy, thanks to the fact that it contributes to improving pollution levels and mitigating climate changes made from a certain responsibility by human beings. Opportunities for wind development were identified through the proposal of four wind farms in different municipalities of the Boyacá Department with a total installed capacity of 52.5 MW through 21 wind turbines of nominal power of 2.5 MW per year with load factors higher than the global weighted average of the 2017 for onshore wind energy. In the evaluation of the projects, positive financial indicators are obtained that make the projects attractive, generating jobs, quality of life and going hand in hand with the environment for the Department of Boyacá.
Keywords: Environment; wind energy; energy sources; winds